2023
DOI: 10.3390/su15032383
|View full text |Cite
|
Sign up to set email alerts
|

Digital Financial Inclusion: COVID-19 Impacts and Opportunities

Abstract: The COVID-19 pandemic has caused the acceleration of digitization and the consideration of digital financial inclusion as a means to minimize negative economic consequences and increase the resilience of households and SMEs. The purpose of this article was to assess the impact of the COVID-19 pandemic on digital financial inclusion by constructing and calculating an integral index of digital financial inclusion (DFI) based on Global Findex Database indicators. The approach to calculating the DFI index and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Tay et al (2022) in their systematic review of literature, explore the role of digital financial inclusion in achieving sustainable development goals (SDGs) across various countries and conclude that even if digital finance has the potential to reduce poverty in the developing countries (mainly Asian), there exist significant inequalities in terms of income, gender and rural–urban residence that act as bottlenecks to spread of digital financial inclusion. A recent study by Dluhopolskyi et al (2023) used Global Findex Data of 2014, 2017 and 2021 for 142 countries to construct passive and active digital financial inclusion Index to analyze the impact of Covid-19 pandemic on digital financial inclusion. The analysis indicates significant disparity across groups of countries from different income levels in terms of digital financial inclusion, with developing countries being the most vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tay et al (2022) in their systematic review of literature, explore the role of digital financial inclusion in achieving sustainable development goals (SDGs) across various countries and conclude that even if digital finance has the potential to reduce poverty in the developing countries (mainly Asian), there exist significant inequalities in terms of income, gender and rural–urban residence that act as bottlenecks to spread of digital financial inclusion. A recent study by Dluhopolskyi et al (2023) used Global Findex Data of 2014, 2017 and 2021 for 142 countries to construct passive and active digital financial inclusion Index to analyze the impact of Covid-19 pandemic on digital financial inclusion. The analysis indicates significant disparity across groups of countries from different income levels in terms of digital financial inclusion, with developing countries being the most vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address the pressures of the COVID-19 pandemic, many banking establishments made use of information technologies to optimize the delivery of their services and overcome accessibility problems, resulting from restrictions imposed by governments to prevent the spread of the virus. In the run-up to the COVID-19 pandemic, the development of innovative technologies such as Artificial Intelligence, the Internet of Things, Blockchain, the growth of FinTech, and the presence of social networks have influenced the financial market and the availability of services for consumers [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The confinement caused serious macroeconomic affectation for many countries, negatively impacting the social and ecological sphere. However, at the same time, there was an accelerated growth of new digital technologies, where opportunities were seen to minimize the negative consequences of the crisis, so that "digital financial inclusion has become a key aspect of household and SME resilience" [32]. To measure the impact of COVID-19 on technology engagement, the authors constructed a digital inclusion index.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in this field demonstrated that increased financial inclusion substantially reduces poverty and income inequality rates [ 9 , 10 ]. The COVID-19 pandemic has accelerated digital financial inclusion, turning it into a potent tool for enhancing financial access and offering assistance to individuals and households during and after the pandemic [ 11 , 12 ]. However, there is scarce literature addressing the impact of financial inclusion on the financial hardship related to health and medical expense concerns.…”
Section: Introductionmentioning
confidence: 99%